PERBUATAN MANUSIA DALAM PANDANGAN HADIS TELAAH PEMIKIRAN HADIS DALAM PANDANGAN MUHAMMAD AL-GHAZALI - Hadi, Muhammad Khoirul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
This study is a research-based research is research library which starts from understanding the traditions relating to human actions, in this case the actions of people who exist in the understanding of the traditions of the prophet were analyzed using Matan pendektan and critical theory ala Muhammad al-Ghazalii, the da two important questions in this study, the first of how the views of Muhammad al-Ghazali against the traditions of the human actions in relation to understanding jabariyyah and Qadariyyah, both how the biography of the life of Muhammad al-Ghazali al.hasil of this study is, first that Muhammad al-Ghazali criticized traditions of human actions according to the jabriyyah and feed space impartial understanding with a view Qadiriyyah. Both figures dalah know boigrafi Muhammad al-Ghazali, sebgai contemporary thinkers capable hadith in Muslim world.